Variant call format (VCF) file corresponding to called single nucleotide polymorphisms (SNPs) from a set of 454 clone-corrected isolates of Fusarium graminearum (Dhakal et al., submitted) - Dhakal, Upasana; Toomajian, Christopher; Leslie, John F.; Yue, Wei (My University, 2023)
VCF file (fileformat=VCFv4.2, readable without specialized software) with genotyping-by-sequencing SNPs from set of 454 clone-corrected isolates of Fusarium graminearum, from the US and Uruguay. Produced by GATK software v. 4.1.8.1, only biallelic SNPs retained. SNPs from this file segregated in a larger sample of over 500 isolates (some from closely related species), and what remains in this file were selected after variant quality score recalibration (vqsr).